THE URBAN MODERNIZATION OF THE CITY OF ALGIERS, WHAT TOOLS? - Naziha Laouissi (International Journal of Innovative Technologies in Social Science, 2024)
Being the result of a state voluntarism, traditional planning, which has for a long time forged urban development in Algeria, has proved to be an ineffective tool. Lacking the major urban strategies capable of creating considerable endogenous development, it has generated human settlements with landscapes of lesser urban quality, if not unpleasant. Its failure and obsolescence have led to the adoption of new urban planning practices, in this case: the project approach. With the advent of globalisation, major urban projects or major structural and emblematic projects have met with a favourable response in other parts of the world, making cities more attractive and more competitive. This problem made us, in the present work, target the city of Algiers as a case study in order to identify the urban planning instruments adopted and the measures taken, in particular, the modifications made to the P.D.A.U.1 for the upgrading of the capital. The aim of this work is to improve the tools of urban production of this case.